2021
DOI: 10.21203/rs.3.rs-823581/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preventive Effect of Lactobacillus Plantarum HFY15 on Oxidative Damage and Acute Liver Injury Induced by Carbon Tetrachloride (CCl 4 ) in Mice

Abstract: BackgroundCarbon tetrachloride (CCl4) is a widely used hepatic toxin that causes acute liver injury through pathological mechanisms such as oxidative stress, inflammation, and apoptosis. In this experiment, mice were treated with Lactobacillus plantarum (LP) HFY15, silymarin, and Lactobacillus delbruechii subsp. bulgaricus (LDSB) for two weeks, and intraperitoneal injection of CCl4-induced acute liver injury to study the preventive effect of LP-HFY on CCl4-induced acute liver injury, especially in oxidative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…IL-1, IL-6 and TNF- are important inflammatory factors in the body. After the body has an inflammatory response, the level of inflammation in the body will increase significantly [23,24] . The results in Table 3 showed that the serum levels of inflammatory cytokines in the Model group were significantly increased.…”
Section: Effect Of Aqueous Extract Of Spatholobi Caulis On Serum Infl...mentioning
confidence: 99%
“…IL-1, IL-6 and TNF- are important inflammatory factors in the body. After the body has an inflammatory response, the level of inflammation in the body will increase significantly [23,24] . The results in Table 3 showed that the serum levels of inflammatory cytokines in the Model group were significantly increased.…”
Section: Effect Of Aqueous Extract Of Spatholobi Caulis On Serum Infl...mentioning
confidence: 99%